Topics of QQML - Lasić-Lazić, Jadranka; Lazić, Nikolaj; Zorica, Mihaela Banek (Qualitative and Quantitative Methods in Libraries; 2015: Special Issue: Bibliometrics, 2017)
The paper gives an overview of topics that have been highlighted at the previous five QQML conferences. Based on the classification of conference papers, we will show how much interest there was in particular topics, the institutions that authors came from, etc. We will also give a historiograph presentation of how specific research topics appeared through time. We will use statistical indicators relating to the number and type of conference papers, topics, keywords and co-authorship to show and analyse productivity in the field of information sciences taken as a whole. In this context, we will particularly analyse institutions and countries that authors came from. Finally, we will especially single out those indicators that expressly show the conferences' impact over this five-year period. The aim of the paper is to show the significance of conferences in the development of the fields.